PEMANFAATAN PLATFROM MERDEKA MENGAJAR (PMM) DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMPN 1 PONTANG - Moch Abdul Rohman; Anisa Fauziyah; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Independent Curriculum, initiated by the Ministry of Education and Culture, serves as a strategic measure to enhance the quality of national education. It offers teachers the Independent Teaching Platform, intended not only for instructional purposes but also for their ongoing learning and innovation. The research seeks to explore how the implementation of this platform in schools aligns with the Independent Curriculum. Employing qualitative research methods, the study employs questionnaire-based data collection, with findings presented in qualitative descriptive format. The findings underscore the pivotal role of the Independent Teaching Platform in curriculum execution within educational institutions. Teachers at SMP Negeri 1 Pontang have embraced the Platform to hone their skills and effectively execute the Independent Curriculum. Noteworthy features of the Independent Teaching Platform include inspirational videos, teaching resources, self-paced training modules, portfolio showcasing, collaborative communities, and student evaluations.